Factors Driving Sustainability of Food and Beverage Industries - Muzakar Isa; Aflit Nuryulia Praswatia; Siti Zulaekah (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2024)
This study has two objectives, namely compiling and analyzing vulnerability indexes of business unit, and analyzing key success variables for food and beverage industries after the COVID-19 pandemic. The analysis tool used in this study is business vulnerability analysis. The vulnerability analysis is derived from the vulnerability index to the COVID-19 threat, which is collected from all aspect indicator values of MSMEs' vulnerability to the COVID-19 theeat. These values consist of exposure, sensitivity, and adaptive capacity. The results of the study explain that food and beverage MSMEs are categorized into medium vulnerability to the threat of COVID-19, where sensitivity is the highest influence aspect as a determinant of the vulnerability level. Due in part to the high number of MSMEs that are sensitive to the threat of COVID-19 and lack the ability to adjust, there may have been a fall in sales and bankruptcy of food and beverage MSMEs during the COVID-19 pandemic.